Laboratory Diagnosis of Malaria: Comparison of Manual and Automated Diagnostic Tests - Samina Naz Mukry; Madiha Saud; Gul Sufaida; Kashif Shaikh; Arshi Naz; Tahir Sultan Shamsi (Canadian Journal of Infectious Diseases and Medical Microbiology)
Malaria is the second most prevalent disease in Pakistan resulting in ~30,000 annual deaths. In endemic countries like Pakistan precise and timely diagnosis of malaria is imperative to overcome the associated risks of fatal outcomes. Malarial parasite was screened in 128 malaria suspected patients and 150 healthy controls, by species-specific PCR, microscopy of blood smears, hemoanalyzer Sysmex XE-2100, and rapid test devices (First Response Malaria® and ICT Malaria Combo®). The microscopy detected MP in 126 samples (parasite load/µl 386–53712/µl); 71.094% were infected with Plasmodium vivax and 14.844% with P. falciparum while 14.062% had mixed P. vivax and P. falciparum infection. The mean parasite load for P. vivax and P. falciparum was 14496/µl and 24410/µl, respectively. The abnormal scattergrams of DIFF, WBC/ Baso, IMI channel, and RET-EXT on Sysmex XE-2100 supported 99.2% parasite detection, whereas only 93% of confirmed malaria cases were detected by both rapid tests. About 127 samples were positive by PCR. Since Sysmex XE-2100 automatically detected the presence of malarial parasite with high sensitivity, it can be a good option for presumptive diagnosis in endemic areas. Microscopy remains the gold standard to confirm MP in suspected patients. Rapid diagnostic tests have acceptable sensitivity and specificity.